ANALISIS PENGANGKATAN KEPALA DAERAH YANG MENYIMPANGI PUTUSAN MK NO 15/PUU-XX/2022 DAPAT MENGGARADASI HUKUM - Gabriel Frans Possenti Masyur Marung; Yusuf Muhamad Said (The Juris, 2022)
In the elucidation of the Constitution of the Republic of Indonesia, it is emphasized that Indonesia is not based on power (machstaat) but based on rechtsstaat or law. The definition of machstaat includes, "Ligitimizing State Actions Based on Power". That authority is translated, the government can give the ability to carry out certain legal actions intended to cause legal consequences, including the emergence and disappearance of certain legal consequences. Thus, rechstaat should not be translated, someone can act on behalf of the government or the state to carry out or take legal action, arguing that the state wants to create justice, as if everything must be acceptable to the public. This study will analyze legal issues, facts, and other legal phenomena related to the legal approach. Research in the form of juridical, descriptive with its analysis limits the issue of appointing regional heads ahead of the 2024 presidential election which ignores the considerations of the Constitutional Court Decision. This method will not conclude that regional elections are generally accepted regarding the appointment of regional heads outside of their standard. In conclusion, the Judicial Review of Article 201, Law Number 10 of 2016 concerning Pilkada which the Constitutional Court Judges consisting of the Chairman, Anwar Usman, and its members in their Amar Decision rejected the petition of the Petitioners in its entirety. The discussion occurred because the rejection of the lawsuit was inconsistent with considerations that seemed to open up space for the public or civil society to demand an open and democratic government in appointing regional heads ahead of the 2024 presidential election.